The Effect of Covid-19 Pandemic anxiety on Breastfeeding Expenditure on Post Partum Mothers in Air Putih Bengkalis Village Health Center Working areas - Susanti, Komaria; Fatma Nadia; Sulis Tyarini (Universitas STRADA Indonesia, 2023)
The Covid-19 pandemic has caused many restrictions on almost all routines services, both in terms of access and quality, including restrictions on maternal and neonatal health services, such US a reduction in the frequency of antenatal care and postponement of classes for pregnant women. This condition can cause psychological problems for postpartum mothers, which can cause anxiety, the impacts of anxiety can cause breast milk production to not run smoothly and afraid of contracting Covid-19. The purpose of the study was to determine the effect of the Covid-19 pandemic anxiety on breastfeeding mothers post partum in the Air Putih village, the working area of the Bengkalis health center . The time of the research was carried out in June-July 2021. The place of research was carried out in the Air Putih village. The sample in this study were 32 respondents with a total sampling technique. The research instrument used the HARS questionnaire. Data analysis was carried out univariate and bivariate. Univariate results showed that the majority of anxiety levels experienced moderate anxiety with a percentage of 43.8%. The frequency of expulsion of breast milk in the majority of post partum mothers are not smooth with a percentage of 71.9%. The results of the bivariate analysis using the likelihood ratio test showed that the p value was 0.016 <0.05. the conclusion is that there is an influences of the anxiety of the Covid-19 pandemic on the expenditure of breast milk for post partum mothers in the Air Putih village, the working area of the Bengkalis health center . It is hoped that post partum mothers will not b too anxious about the transmission of covid-19 so that breastfeeding can continue smoothly and maintain health protocols during the covid-19 pandemic.